Subclinical malignant catarrhal fever cases in Bali cattle detected in some abattoirs by means of histopathological examination - Damayanti, Rini (Indonesian Animal Sciences Society, 1995)
Surveys were conducted in Mataram (West Nusa Tenggara), Banyuwangi (East Java), Kendari (South East Sulawesi), and Denpasar (Bali) and 413 histopathological specimens were collected from Bali cattle slaughtered in abattoirs . Subclinical malignant catarrhal fever cases were found histologically with the incidence rates as follows : 22 .9% (Mataram, December 1988), 3 .1 % (Mataram, March 1992), 8.8% (Mataram, March 1993), 11 .1% (Banyuwangi, January 1993), 1 .3 % (Kendari, February 1994), and 4 .6% (Denpasar, August 1994) . Totally, from 413 samples examined, the subclinical MCF cases occurred in 36 cattle (8 .6%) . Key words: Malignant catarrhal fever, subclinical, histopathology, Bali cattle, abattoir